Study of The Effect of Heating During Fabrication On The Insulation Resistance of The 75 Mw Generator Stator at the Malea Energy Stage-2 BMS PLTA - Rompon, Aldy; Suhardi, Iwan (Energy Insights, 2025)
This study aims to assess the impact of heating during fabrication on the insulation resistance of the 75 MW generator stator at the Malea Energy Stage-2 BMS hydroelectric power plant. Using a quantitative descriptive method and documentation for data collection, researchers analyzed secondary data archived by staff at the plant. The results showed a significant increase in insulation resistance from 6,930 MΩ at 39°C to 16,300 MΩ at 80°C. The Arrhenius equation revealed an activation energy of 19,083.41 J/mol, indicating good thermal resistance. A linear regression analysis showed a strong positive relationship between temperature and insulation resistance, with a correlation coefficient (R) of 0.9915 and an R^2 value of 0.9831. The heating process met the Toshiba SF80.35-12/5200 standard and the National Standard of the People’s Republic of China, proving effective in reducing humidity, accelerating resin hardening, and improving insulation durability.